2018
DOI: 10.3389/fpls.2018.00341
|View full text |Cite
|
Sign up to set email alerts
|

Transcript Profiling Identifies NAC-Domain Genes Involved in Regulating Wall Ingrowth Deposition in Phloem Parenchyma Transfer Cells of Arabidopsis thaliana

Abstract: Transfer cells (TCs) play important roles in facilitating enhanced rates of nutrient transport at key apoplasmic/symplasmic junctions along the nutrient acquisition and transport pathways in plants. TCs achieve this capacity by developing elaborate wall ingrowth networks which serve to increase plasma membrane surface area thus increasing the cell's surface area-to-volume ratio to achieve increased flux of nutrients across the plasma membrane. Phloem parenchyma (PP) cells of Arabidopsis leaf veins trans-differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 82 publications
0
4
0
Order By: Relevance
“…7 d and e), which suggests that developmental processes are coupled with 5mC to some degree. The counterparts of some common genes in A. thaliana are involved in cell growth ( CCR4 [ 60 ] , MAP 70–1 [ 61 ] , and UGT85A [ 62 ]), secondary cell wall biosynthesis ( NAC056 [ 63 ] , PAL1 [ 64 ], FLA11 [ 65 ], C4H [ 66 ], and MYB52 [ 67 ]), and hormone and signal transduction ( WRKY27 [ 68 ] , UGT84B1 [ 69 ], anac047 [ 70 ], PIP1 [ 71 ] , and CYP716A1 [ 72 ]) (Additional files 15 and 16 ), indicating that methylation can affect some individual pathway or regulatory genes involved in wood formation. For example, expression of PtrPAL2 (Potri.008G038200) increased dramatically with the change of DNA methylation sites in PS vs TS (Additional file 15 ).…”
Section: Discussionmentioning
confidence: 99%
“…7 d and e), which suggests that developmental processes are coupled with 5mC to some degree. The counterparts of some common genes in A. thaliana are involved in cell growth ( CCR4 [ 60 ] , MAP 70–1 [ 61 ] , and UGT85A [ 62 ]), secondary cell wall biosynthesis ( NAC056 [ 63 ] , PAL1 [ 64 ], FLA11 [ 65 ], C4H [ 66 ], and MYB52 [ 67 ]), and hormone and signal transduction ( WRKY27 [ 68 ] , UGT84B1 [ 69 ], anac047 [ 70 ], PIP1 [ 71 ] , and CYP716A1 [ 72 ]) (Additional files 15 and 16 ), indicating that methylation can affect some individual pathway or regulatory genes involved in wood formation. For example, expression of PtrPAL2 (Potri.008G038200) increased dramatically with the change of DNA methylation sites in PS vs TS (Additional file 15 ).…”
Section: Discussionmentioning
confidence: 99%
“…Together with the regular phi thickenings, this structure appeared similar to crescent thickenings in the root cortex of red bayberry ( Myrica rubra ) and wax apple ( Syzygium samarangense ) [ 5 , 6 ]. Work by Fernandez-Garcia, Lopez-Perez, Hernandez, and Olmos [ 15 ] in B. oleracea showed high ATPase activity localised to so-called wall ingrowth regions, an area equivalent to where reticulate networks are located, while Zelko, Lux, and Czibula [ 25 ] indicated that the increased surface area in the intercellular space adhering to the cortical thickenings may play a similar role to transfer cells [ 39 ] by increasing plasma membrane surface for enhanced transport capacity. However, these “wall ingrowth” structures are highly lignified and thus structurally different from the non-lignified, primary wall-like wall ingrowths which characterise most transfer cells [ 38 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, transfer cells (TCs), which can differentiate from existing vascular or non-vascular cell types (e.g., bundle sheath, xylem or phloem parenchyma cells), and which are characterized by prominent plasma membrane ingrowths, have been suggested to be a site of intense transport activity between the different vascular cell types [63]. Most studied in the phloem of minor veins, TC development occurs quite early (after an average of 10 days of growth) in cotyledons as well as in young leaves of Arabidopsis thaliana plants grown in normal conditions [64]. In adult leaves, a basipetal gradient of wall ingrowth deposition that has parallels with the sink/source transition is observed [64].…”
Section: Going In and Out Of The Vascular System: The Role Of Specmentioning
confidence: 99%
“…Most studied in the phloem of minor veins, TC development occurs quite early (after an average of 10 days of growth) in cotyledons as well as in young leaves of Arabidopsis thaliana plants grown in normal conditions [64]. In adult leaves, a basipetal gradient of wall ingrowth deposition that has parallels with the sink/source transition is observed [64]. Additionally, TCs can develop in response to changing environmental conditions, most probably as a result of an increased demand for solute transport [65].…”
Section: Going In and Out Of The Vascular System: The Role Of Specmentioning
confidence: 99%